Improving Teacher Competence in Utilizing Google Workspace for Digital Learning - Ayu Susilawati, Endang; Astuti, Eka Yuni; Sugianto, Didik; Pramesti, Gita; Herianto; Susilo, Andi; Susanto, Herry (JEPTIRA, 2025)
This community service initiative was designed to enhance teachers competencies in utilizing Google Workspace tools specifically Google Drive, Google Slides, and Google Forms to support the integration of digital learning. Conducted through an in-person workshop on February 11, 2025, the training targeted high school and vocational school teachers in the Bekasi region. The session emphasized mastery of essential features, including cloud-based file management, creation of engaging presentations, and the development of online surveys and assessments. The outcomes revealed that participants showed a significant improvement in their ability to operate these digital tools and expressed a strong intention to integrate them into their teaching practices. Overall, this activity contributed meaningfully to the advancement of digital transformation in secondary education settings.